Food consumption and anthropometric evaluation of students in elementary school: literature review - LEAL, Adriele Nayara Cruz (2023)
Food presents as a vital necessity, necessary for the conservation of life and well-being of individuals. This process is considered a basic requirement for health promotion, contributing to human growth and development with quality. Healthy food is one that keeps the body in a state of health, when it prioritizes adequate food, in quantities and quality, at the right times, and that contains varied nutrients to achieve satisfactory benefits for the health of the body and thus contribute to the acquisition of quality of life (BUSATO et al., 2021). The objective of this work was to discuss the main factors associated with Food Consumption and Nutritional Status of schoolchildren, based on a critical review on the subject. To review the topic, the following databases were consulted: BIREME and CAPES journal, covering the period from 2018 to 2021. The descriptors used in the search were: "food consumption", "nutritional assessment", "nutritional status," " school” and “school health”. The research results indicate, through the analysis of the scientific literature, a low consumption of in natura and healthy foods among schoolchildren, in addition to the high consumption of processed and ultra processed foods, resulting in changes in the nutritional status and consequently in the health of the investigated population, with the presence of overweight and obesity, dyslipidemia and increased blood glucose, predisposing factors for cardiovascular diseases. Thus emphasizing the importance of the debate on the subject in future research.